IMPOLITE READER’S RESPONSES ON ONLINE BBC NEWS COMMENTS - Suhaila, Izzati; Mono, Umar; Lubis, Syahron (JAMI: Jurnal Ahli Muda Indonesia, 2022)
Objective: This research was titled “Impolite Reader’s Responses on Online BBC News Comments”. This research found out the impoliteness strategies on BBC News comments. Materials and Methods. The research used a qualitative method. The data were the BBC News Comments. The data were analyzed by the theory of Culpeper. Results. Based on the data analysis found that the data of impoliteness strategy consisted of fifty responses, such as positive impoliteness, negative impoliteness, sarcasm and mock, and bald on record. Positive impoliteness strategy gained 26 utterances (54%) which contained 7 utterances (14%) for inappropriate identity markers, 6 (12%) for ignorance, 4 (8%) utterances for discussing a sensitive topic, 2 utterances (4%) for each secretive language and taboo words, and only one (2%) utterance for disinterested. Then, it was followed by a negative impoliteness strategy that gained 16 utterances (30%), which contained 8 utterances (16%) for condescending, 5 utterances (10%) for explicitly associating, and 2 utterances (4%) for frightened. While, sarcasm and mock gained 6 utterances (12%), and bald on record only gained 2 utterances (4%) for dismissal. Conclusion. The use of the impoliteness strategy in this data conveys an impolite response by using some of the characteristics of the impoliteness strategy. From all types of impoliteness, with-holding impoliteness strategy can’t be found in this research because it should be mostly found in direct two-way interactions rather than responses in the commentary column.